The Effect of Imagery Exercises on The Accuracy Petanque's Game Pointing - Tatang Iskandar; Azi Faiz Ridlo; Domi Bustomi; Hasan Basri (Universitas PGRI Palembang, 2023)
This research is motivated by the inconsistent ability of novice club petanque unisma athletes who will participate in championships between students and other championships. The purpose of the study was to determine the effect of video imagery training on increasing the accuracy of pointing novice athletes at club petanque Unisma Bekasi. This study used an experimental method with a One-Group Pretest-posttest design. The population of 16 novice athletes with sampling techniques with a total sampling of which 16 athletes were sampled. Based on the calculation results, the value of Tcount = 2.445 is obtained, which if we compare with the critical limit of acceptance and hypothesis rejection on dk = (n-1) (16-1) = 15 with a real level (a) = 0.05 obtained t (0.975 : 15) = 2.13. Then it can be concluded that the hypothesis is accepted or in other words there is a significant increase in the hail of the Video Imagery exercise.